Variable expression and penetrance in Portuguese families with Familial Hypercholesterolemia with mild phenotype. (March 2019) - Gaspar, I.M.; Gaspar, A.
Abstract: Familial hypercholesterolemia is an Mendelian dominant disorder characterized by defects of the low density lipoprotein receptor (LDLR) that result in a defective removal of LDL from plasma, which promotes deposition of cholesterol in the skin (xanthelasma), tendons (xanthomas), and arteries (atherosclerosis). Diagnosis severe clinical phenotype FH with Dutch Lipid Clinic Network Criteria, encompassing history of premature ASCVD, tendon xanthomas, and a family history of hypercholesterolemia and premature ASCVD in relatives is rare in the Portuguese FH patients. There is a variability of the phenotype in FH individuals with clinical diagnosis or genetic mutation (carriers and patients) probably due to environmental factors in the last century, a Mediterranean diet, or a diet without fat food, trans fat food, no smoking, no sedentary life that can interfere with our metabolism, or are consequences of polygenic, epigenetic, acquired defects, modifiers genes and beta-globin asymptomatic carriers. We have several concepts/mechanisms in genetics that are transversal to hereditary diseases and common in FH, such as somatic mosaicism, germinal mosaicism, variable expression and variable penetrance of mutations. A negative blood genetic test result does not exclude FH, because the pathogenic LDLR mutation can be expressed only in the liver (a mutation in somatic tissue) or occasionally there is a vertical transmission from partner to future child by a mutation on germinal line - germinal mosaicism. Unlike north European countries, the most FH carriers and patients had less severe phenotypes, for example with have children and young adult carriers with LDL-R mutation had normal TC and LDL-C, old women had a milder phenotype without ASCVD events, tendon xanthomas are seen in <1% patients, and most homozygous FH patients are under combined therapy.